Thermal performance improvement of PCM layers - Rubén D. Santiago-Acosta; José A. Otero; Ernesto M. Hernández-Cooper (Energy Reports, 2023)
Thermal shielding through phase change material wallboards exposed to oscillating temperature conditions has been previously studied by several authors. PCM layers provide thermal comfort by releasing(absorbing) latent heat energy, constituting a sort of active cooling(heating) system produced by the dynamics of liquid-solid interfaces. In this work, the effect of volume displacements in the thermal performance of PCM wallboards is analyzed. The thermal energy released(absorbed) at the inner wall is greatly affected by the dynamics of volume displacements and the formation of one or more interfaces, when exposed to temperature oscillations around the melting point of the material. Equations of motion for the thickness of the PCM layer and interfaces, are derived. Volumetric effects produced by the sharp density change of liquid-solid transitions as well as the thermal expansion of each phase are considered in the analysis. We found that the term proportional to the expansion coefficient that appears in the equations of motion is negligible. The effect is hidden by volume displacements produced through the density difference between phases. Semi-analytical methods were used to solve the equations of motion described in this work. We found that the thermal energy released(absorbed) is deeply affected by the initial configuration of phases and the time instant of exposure to ambient conditions. Thermal shielding can be improved through PCM preparation and time of installation, according to the results found in this work. Finally, examples with two alkanes are provided when the external wall is exposed to different weather conditions.